2007
DOI: 10.1080/10401230701334606
|View full text |Cite
|
Sign up to set email alerts
|

Are There Any Differences in the Efficacy among Second Generation Antipsychotics in the Treatment of Schizophrenia and Related Disorders?

Abstract: Possible new studies should focus on long-term effects, including cost-effectiveness, quality of life, social functioning and service utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Of two recent reviews, one concluded that it was difficult to distinguish atypical antipsychotic drugs in terms of efficacy134 while the other concluded that there were significant differences in both efficacy and tolerability 135. Nevertheless, amisulpride may offer advantages over other atypical antipsychotic drugs in the treatment of negative and depressive symptoms, and tolerability advantages such as the avoidance of weight gain 136…”
Section: Discussion: Differential Indications For Amisulpride?mentioning
confidence: 99%
“…Of two recent reviews, one concluded that it was difficult to distinguish atypical antipsychotic drugs in terms of efficacy134 while the other concluded that there were significant differences in both efficacy and tolerability 135. Nevertheless, amisulpride may offer advantages over other atypical antipsychotic drugs in the treatment of negative and depressive symptoms, and tolerability advantages such as the avoidance of weight gain 136…”
Section: Discussion: Differential Indications For Amisulpride?mentioning
confidence: 99%
“…Collectively, these findings suggest that amisulpride is an atypical antipsychotic drug with a lower risk of weight gain. Both amisulpride and ziprasidone were preferred to olanzapine in patients who had recently experienced weight gain 40,41. This makes sense because second-generation antipsychotics do not appear to differ regarding efficacy, but both amisulpride and ziprasidone have been shown to cause less weight gain than other compounds 38,42,43…”
Section: Amisulpride: Safety and Tolerabilitymentioning
confidence: 99%
“…First-generation (conventional) and second-generation (atypical) antipsychotics are eff ective in treating the positive symptoms associated with these disorders, but effi cacy for negative symptoms and cognitive dysfunction is an unmet need. Considerable accumulated data suggest that antipsychotics diff er more in terms of safety and tolerability than effi cacy [18,25] . Asenapine is an atypical antipsychotic approved in the United States of America for the acute treatment of schizophrenia in adults and for the…”
Section: Introduction ▼mentioning
confidence: 99%